Sodium hypochlorite as an alternative to hydrogen peroxide in Fenton process for industrial scale. (15th September 2017) - Behin, Jamshid; Akbari, Abbas; Mahmoudi, Mohsen; Khajeh, Mehdi
Abstract: In present work, the treatment of aromatic compounds of simulated wastewater was performed by Fenton and NaOCl/Fe 2+ processes. The model solution was prepared based on the wastewater composition of Diisocyanate unit of Karoon Petrochemical Company/Iran containing Diamino-toluenes, Nitro-phenol, Mononitro-toluene, Nitro-cresol, and Dinitro-toluene. Experiments were conducted in a batch mode to examine the effects of operating variables such as pH, oxidant dosages, ferrous ion concentration and numbers of feeding on COD removal. Taguchi experimental design was used to determine the optimum conditions. The COD removal efficiency under optimum conditions (suggested by Taguchi design) in Fenton and NaOCl/Fe 2+ processes was 88.7% and 83.4%, respectively. The highest contribution factor in Fenton process belongs to pH (47.47%) and in NaOCl/Fe 2+ process belongs to NaOCl/pollutants (50.26%). High regression coefficient (R 2 : 0.98) obtained for Taguchi method, indicates that models are statistically significant and are in well agreement with each other. The NaOCl/Fe 2+ process utilizing a conventional oxidant, in comparison to hydrogen peroxide, is an efficient cost effective process for COD removal from real wastewater, although the removal efficiency is not as high as in Fenton process; however it is a suitable process to replace Fenton process in industrial scale for wastewater involved aromatic compounds with high COD. This process was successfully applied in Karoon Petrochemical Company/Iran. Graphical abstract: Highlights: Sodium hypochlorite was used instead of hydrogen peroxide in Fenton process. NaOCl/Fe 2+ process is efficient for removal of aromatics from industrial wastewater. NaOCl/Fe 2+ is a cost-effective process working in a slightly wider range of pH.